KAJIAN KAPASITAS LENTUR PLAT BETON BERTULANGAN BAMBU WULUNG POLOS (ALTERNATIF PENGGANTI TULANGAN BAJA PADA PLAT LANTAI) - Juwanto Juwanto; Agus Setiya Budi; Kusno Adi Sambowo (Program Studi Teknik Sipil FT UNS, 2014)
The increasing of population will lead to increased need for housing. Market demand for steel reinforcement as a basic material in the constructionof residential houses will go up automatically . In fact, as we know that the iron ore as the raw material of steel is limited in nature and can not beupdated . Hence, there is need for the study of materials that allow to substitute steel reinforcement , one of which is bamboo . This research examinedhow the ratio of flexural capacity of steel reinforced concrete plate and bamboo Wulung . This study uses an experimental laboratory and implementedin Materials Laboratory and Structures Laboratory , Faculty of Engineering , Sebelas Maret University. Reinforcement bamboo usedplain ( without notch ) and dimensions of 5.2 mm x 10 mm with an area equivalent diameter of 8 mm steel reinforcement to be used as a comparison. Specimens used in the form of 3 concrete plate with steel reinforcement and 3 concrete plate with bamboo reinforcement. Same specimen size ,which is 600 mm x 400 mm x 100 mm and tested with third-point loading method . Bending capacity test will be done when the specimen was28 days . From the test results obtained the mean value of flexural capacity of steel reinforced concrete plate is 0.5262 ton.m and from bambooWulung is 0.1678 ton.m.